Numerical Procedure for Modeling Crack Closure Induced Plasticity - Julendra Bambang Ariatedja; Wajan Berata (IPTEK The Journal of Engineering, 2023)
Numerical procedures are utilized to predict crack closure-induced plasticity on planar surfaces. Skinner's algorithm is presented as an APDL macro command set. Procedures for controlling element size are developed to ensure the continuity of element size gradation. A loading generator is constructed using the *dim parameter, and the Newman model is explored for comparison. The analysis, based on conducted research, yields results lower than 0.05Sy.